Ṭarīqa Followers and Inner Peace: A Phenomenological Study of Naqshbandiyya-Khālidiyya Order in Indonesia - Nurul Qomariyyah; Ahmad Saifuddin (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2022)
This paper aims to reveal the inner peace dynamics of followers of the Naqshbandiyya-Khālidiyya Order. It employs a qualitative approach with the phenomenological method and in-depth analysis to describe the followers' inner peace dynamics. Interviews and observations have been carried out to collect data. Data reduction, presentation, conclusion drawing, and verification are employed. This study reveals that reaching inner peace dynamics needs problem-solving. The second step is making the decision. The third step is finding the solution to solve the problems to find the right strategy for a particular situation. The fourth step is being patient by emotional restraint. The last step is embracing faith and self-efficacy in dealing with problems. Faith is obtained from dhikr as it will lead to remembering God. The stages and aspects of inner peace are different from Mujib and Mudzakkir's theory. In addition, this study found that internalizing the value of murshid and self-approach to God positively impact inner peace.Contribution: This article contributes to a new finding about the stages of achieving mental peace. So, everyone can seek peace of mind through these various stages. In addition, the Ṭarīqa can also optimize its role because the murshid is considered necessary for increasing peace of mind.